The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al. (EMBO Molecular Medicine)
Keywords: Molecular Medicine

Metamodellbasierte Prozesskette - Umformen-Schneiden-Spannen-Fügen - Heyser, Per; Meschut, Gerson; Nehls, Thomas; Scharr, Christian; Froitzheim, Pascal; Flügge, Wilko; Wiesenmayer, Sebastian; Merklein, Marion (Pressen, Systeme, Prozesse der Zukunft Effizienz + Digitalisierung)

Konzeption einer adaptiven Prozesskette für das mechanische Fügen - Meschut, Gerson; Heyser, Per; Merklein, Marion; Wiesenmayer, Sebastian; Flügge, Wilko; Scharr, Christian; Nehls, Thomas

Smart process chain – data analysis in sheet metal processing for joinability prediction - Heyser, Per; Wiesenmayer, Sebastian; Nehls, Thomas; Scharr, Christian; Flügge, Wilko; Merklein, Marion; Meschut, Gerson (SMART PRODUCTION 2022: DIGITALIZING AUTOMOTIVE MANUFACTURING)

Investigating the argumentation structures of EFL learners from diverse language backgrounds - Chen, Mei-Hua; Mudgal, Garima; Chen, Wei-Fan; Wachsmuth, Henning (EUROCALL)

Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny

Stress-Aware Periodic Test of Interconnects - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing)
Safety-critical systems have to follow extremely high dependability requirements as specified in the standards for automotive, air, and space applications. The required high fault coverage at runtime is usually obtained by a combination of concurrent error detection or correction and periodic tests within rather short time intervals. The concurrent scheme ensures the integrity of computed results while the periodic test has to identify potential aging problems and to prevent any fault accumulation which may invalidate the concurrent error detection mechanism. Such periodic built-in self-test (BIST) schemes are already commercialized for memories and for random logic. The paper at hand extends this approach to interconnect structures. A BIST scheme is presented which targets interconnect defects before they will actually affect the system functionality at nominal speed. A BIST schedule is developed which significantly reduces aging caused by electromigration during the lifetime application of the periodic test.
Keywords: Electrical and Electronic Engineering

EM-Aware Interconnect BIST - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Procrastination in the Looking Glass of Self-Awareness: Can Gamified Self-Monitoring Reduce Academic Procrastination? - Klingsiek, Katrin; John, Thomas; Kundisch, Dennis (die hochschullehre)

Does it really take a village to raise a child? Reflections on the need for collective responsibility in inclusive education - Subban, Pearl K.; Bradford, Brent; Sharma, Umesh; Loreman, Tim; Avramidis, Elias; Kullmann, Harry; Sahli Lozano, Caroline; Romano, Alessandra; Woodcock, Stuart (European Journal of Special Needs Education)

Broadband optical Ta2O5 antennas for directional emission of light - Farheen, Henna; Yan, Lok-Yee; Quiring, Viktor; Eigner, Christof; Zentgraf, Thomas; Linden, Stefan; Förstner, Jens; Myroshnychenko, Viktor (Optics Express)
Highly directive antennas with the ability of shaping radiation patterns in desired directions are essential for efficient on-chip optical communication with reduced cross talk. In this paper, we design and optimize three distinct broadband traveling-wave tantalum pentoxide antennas exhibiting highly directional characteristics. Our antennas contain a director and reflector deposited on a glass substrate, which are excited by a dipole emitter placed in the feed gap between the two elements. Full-wave simulations in conjunction with global optimization provide structures with an enhanced linear directivity as high as 119 radiating in the substrate. The high directivity is a result of the interplay between two dominant TE modes and the leaky modes present in the antenna director. Furthermore, these low-loss dielectric antennas exhibit a near-unity radiation efficiency at the operational wavelength of 780 nm and maintain a broad bandwidth. Our numerical results are in good agreement with experimental measurements from the optimized antennas fabricated using a two-step electron-beam lithography, revealing the highly directive nature of our structures. We envision that our antenna designs can be conveniently adapted to other dielectric materials and prove instrumental for inter-chip optical communications and other on-chip applications.
Keywords: tet_topic_opticalantenna

Dekonstruktionen des Staatssozialismus (und mehr). Komische Helden der Wende- und Nachwendezeit in deutschsprachiger Literatur - Elit, Stefan (Aufbruch und Krise. Ästhetische/Narrative Auseinandersetzungen mit der spanischen Transición und der deutschen ‚Wende‘ (Germanisch-Romanische Monatsschrift. Beiheft))

Exploration of Location Data: Real Data in the Context of Interaction with a Cellular Network - Höper, Lukas; Podworny, Susanne; Schulte, Carsten; Frischemeier, Daniel (Proceedings of the IASE 2021 Satellite Conference)
Students are not aware and have little understanding of collecting and processing personal data in their everyday contexts of interaction with data-driven digital artifacts. To be aware of where, how and why data are collected and processed is important to be self-determined. Therefore, we develop and evaluate a teaching sequence to provide reasoning about data as a fundamental aspect of statistical literacy. This teaching sequences deals with the context of interaction with a cellular network where location data are collected. Students get real location data from an unknown person which can be explored with the aim to characterize the person. Students gain different insights by using different basic filters and explain how they achieve these. The results of the exploratory study indicate that students learned to gain insights by exploring given location data and that these insights may describe the person with detailed aspects that may not necessarily be true.

Experimental verification of the acoustic geometric phase - Liu, Bingyi; Zhou, Zhiling; Wang, Yongtian; Zentgraf, Thomas; Li, Yong; Huang, Lingling (Applied Physics Letters)
Optical geometric phase encoded by in-plane spatial orientation of microstructures has promoted the rapid development of numerous functional meta-devices. However, pushing the concept of the geometric phase toward the acoustic community still faces challenges. In this work, we utilize two acoustic nonlocal metagratings that could support a direct conversion between an acoustic plane wave and a designated vortex mode to obtain the acoustic geometric phase, in which an orbital angular momentum conversion process plays a vital role. In addition, we realize the acoustic geometric phases of different orders by merely varying the orientation angle of the acoustic nonlocal metagratings. Intriguingly, according to our developed theory, we reveal that the reflective acoustic geometric phase, which is twice the transmissive one, can be readily realized by transferring the transmitted configuration to a reflected one. Both the theoretical study and experimental measurements verify the announced transmissive and reflective acoustic geometric phases. Moreover, the reconfigurability and continuous phase modulation that covers the 2π range shown by the acoustic geometric phases provide us with the alternatives in advanced acoustic wavefront control.
Keywords: Physics and Astronomy (miscellaneous)

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Friedrich Gottlieb Klopstock: Handexemplar der „Oden“. Kritische Edition, hg. v. Marit Müller, Göttingen 2020 (edition Text 18) - Elit, Stefan (Arbitrium 40)

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (arXiv:2205.06560)
Knowledge graph embedding research has mainly focused on learning continuous representations of entities and relations tailored towards the link prediction problem. Recent results indicate an ever increasing predictive ability of current approaches on benchmark datasets. However, this effectiveness often comes with the cost of over-parameterization and increased computationally complexity. The former induces extensive hyperparameter optimization to mitigate malicious overfitting. The latter magnifies the importance of winning the hardware lottery. Here, we investigate a remedy for the first problem. We propose a technique based on Kronecker decomposition to reduce the number of parameters in a knowledge graph embedding model, while retaining its expressiveness. Through Kronecker decomposition, large embedding matrices are split into smaller embedding matrices during the training process. Hence, embeddings of knowledge graphs are not plainly retrieved but reconstructed on the fly. The decomposition ensures that elementwise interactions between three embedding vectors are extended with interactions within each embedding vector. This implicitly reduces redundancy in embedding vectors and encourages feature reuse. To quantify the impact of applying Kronecker decomposition on embedding matrices, we conduct a series of experiments on benchmark datasets. Our experiments suggest that applying Kronecker decomposition on embedding matrices leads to an improved parameter efficiency on all benchmark datasets. Moreover, empirical evidence suggests that reconstructed embeddings entail robustness against noise in the input knowledge graph. To foster reproducible research, we provide an open-source implementation of our approach, including training and evaluation scripts as well as pre-trained models in our knowledge graph embedding framework.

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology